Analisa Perhitungan Perencanaan Gedung Perkantoran STT Pagar Alam Dengan Metode Manual Dan Staad Pro 2007 - Ardi Sudeni; Tarmizi Tarmizi (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2017)
Office building planning Pagar Alam Technology College is one of the efforts to improve the function and role of office buildings. The selection of structural materials to be used for certain buildings is influenced by the height and span of the structure, availability of materials in the market, foundation conditions, local building regulations and architectural considerations. The frame building system consists of horizontal elements (beams), vertical (columns) and floor plates. Tall building frames can be viewed geometrically as a sum of portal frames. In this study, the results of the analysis showed that the diameter of the floor beam 30 x 15 = 8 D 14, roof diameter 30 x 15 = 4 D 12, column diameter 30 X 30 = 6 D 14, floor plate Ø 10 sengkang 100, roof plate Ø 10 sengkang 100, ladder Ø 100 sengkang 100. The analysis uses the 2007 pro station which produces the dimensions of the roof beam 20 x 30, beam dimensions 20 x 40, column 30 x 30 number of reinforcement 8 D 12